The Value Chain Analysis of Go-Jek - Yogi Sari, Oktora; Yuniarti, Rita (International Journal of Psychosocial Rehabilitation, 2020)
Online transportation is one of the newest service innovations in m-commerce. Online transportation service, or ride-sharing, is an individual transportation service where a customer can order a ride through a mobile application and the driver can respond to the order through the applications, and the customer can easily find transportation to commute to other places (time efficiency). Service quality is an important aspect in m-commerce that can determine customer behavior, satisfaction, and intention to use certain products or services. It is argued that service quality provides long-term success and can be a competitive advantage. Therefore, it is important to assess and measure the service quality, especially services provided in an m-commerce environment. A value chain is comprised of the series of events surrounding the development, production, and delivery of a good or service desired by targeted consumers. This is achieved by ensuring that goods gain consumer-recognized value as they move through each step of the chain. In an efficient and effective value chain, this is achieved through coordinating operations in a manner that ensures the involved companies are able to create more consumer-recognized value than their competitors. The aim of this research is to analyze the value chain of online transportation services, focusing on the technology aspect as the source of competitive advantage.